Mandibular anterior crowding: normal or pathological? - Alberto Consolaro; Mauricio de Almeida Cardoso
ABSTRACT The teeth become very close to each other when they are crowded, but their structures remain individualized and, in this situation, the role of the epithelial rests of Malassez is fundamental to release the EGF. The concept of tensegrity is fundamental to understand the responses of tissues submitted to forces in body movements, including teeth and their stability in this process. The factors of tooth position stability in the arch - or dental tensegrity - should be considered when one plans and perform an orthodontic treatment. The direct causes of the mandibular anterior crowding are decisive to decide about the correct retainer indication: Should they be applied and indicated throughout life? Should they really be permanently used for lifetime? These aspects of the mandibular anterior crowding and their implication at the orthodontic practice will be discussed here to induct reflections and insights for new researches, as well as advances in knowledge and technology on this subject.